Madrasah Education Strategies To Build Student Discipline At Amaliyah Private Aliyah Madrasah Tanjung Tiga - Nur Nisa Br Tj, Anggi (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. This study describes the madrasah education strategy to build student discipline at the private madrasah aliyah amaliyah tanjung tiga. Purpose. The purpose of the research is to inform and educate readers that formal educational institutions, namely madrasah, have the ability to shape the character of a disciplined student. Method. This type of research is qualitative research that seeks to describe social phenomena that are developing in the masses today. The data collection techniques used are observation and unstructured interviews, then the data is analyzed objectively and described scientifically by following the procedures for writing scientific papers. Results. The research results found are as follows: First, private madrasah aliyah amaliyah tanjung tiga teachers on various occasions always educate students to always comply with the rules and regulations that apply in the madrasah environment. Second, private madrasah aliyah amaliyah tanjung tiga teachers always provide exemplary examples of discipline to students so that they become role models for them. Third, private madrasah aliyah amaliyah tanjung tiga teachers always carry out internal supervision of the character of students and student discipline, if there are still students who are not disciplined, madrasah teachers conduct early identification of the triggers for these students to become undisciplined Fourth, the head of the private madrasah aliyah amaliyah tanjung tiga conducts periodic evaluations to all madrassa residents which aim to improve things that must be improved for the next day. Fifth, efforts to establish student discipline are carried out in persuasive ways. Conclusion. Madrasah Aliyah Swasta Amaliyah Tanjung Tiga applies an educational approach in enforcing student discipline. Sanctions are educational in nature, including assignments, written reports to parents, suspension, and temporary or permanent deactivation. The habituation of disciplinary attitudes involves arriving on time, homework, manners, and development activities, with optimal support from students' families.